On the Role of Police in Protecting Property - I. A. Kositsyn (Сибирское юридическое обозрение, 2015)
The author considers different police responsibilities concerning protection of property. The focus is made on property protection service, including those under the contracts carried out by nondepartmental security of the internal affairs’ agencies and directly related to the protection of property. The author concludes that it is relevant to set the issue of redundancy of this function. It is stated that another police function, i.e. supervision of legal entities’ security with specific regulations aims is improperly performed.